2022
DOI: 10.1109/tvcg.2022.3150473
|View full text |Cite
|
Sign up to set email alerts
|

Augmenting Immersive Telepresence Experience with a Virtual Body

Abstract: Fig. 1: Head-mounted display telepresence augmented with a virtual body; the participant (side images) is sitting in one place wearing a head-mounted display, but is telepresent in another location through a live streaming camera having a discussion with an experimenter (center image) and can see robot arms in one condition that match their real arms' motions.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 59 publications
0
2
0
Order By: Relevance
“…In this regard, previous studies have shown that 360° videos are effective in inducing presence (e.g., [ 53 ]). Several factors influence this variable, such as camera height or viewer position [ 55 ]. Thus, participants showed an high sense of presence even though they were not physically in the experience, which might have limited the effect of our intervention [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, previous studies have shown that 360° videos are effective in inducing presence (e.g., [ 53 ]). Several factors influence this variable, such as camera height or viewer position [ 55 ]. Thus, participants showed an high sense of presence even though they were not physically in the experience, which might have limited the effect of our intervention [ 54 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the use of VR and AI in education has moved the traditional classroom to a classroom based on smart technology [4], [5]. Furthermore, the global job competition has dictated the progress in educational systems [6].…”
Section: Introductionmentioning
confidence: 99%